PERANAN SEKTOR PERTANIAN DALAM PENGEMBANGAN PEREKONOMIAN WILAYAH PROPINSIJAWA TENGAH (PENDEKATAN ANALIS1S INPUT OUTPUT) - Ropingi, Ropingi; Artanto, Dany (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Contribute of Agriculture sector in Central Java for developing economy is needed, because this sector can absorb employment higher than others.This study aimed at describing the share of agriculture sector in Central Java, especially for economic development with Input Output Analysis Approach. By assessing data from BPS (example PDRB data per sector with multiyear publications, Central Java in Figures), this study found that agricultural sector has highest forward linkages and backward linkages were animal sector which value of forward linkages was 1,1953 and backward linkages was 1.1889. Besides that animal sector (Sektor Peternakan dan hasil-hasilnya) has highest sensitivity Indeks and dispersion indeks. Agriculture sector that need input smallest for producing process or RIA smallest was Umbi-umbian Sector (RIA - 0.0286). Agriculture Sector that highest output demand for producing process or value of RPA highest was Rice Sector (Sektor Padi) with RPA Value = 0.7713.